Modeling synthetic aperture radar computation with Aspen. (August 2013) - Spafford, Kyle; Vetter, Jeffrey S.; Benson, Thomas; Parker, Mike
This case study presents an analytical performance model for the DARPA UHPC streaming sensor challenge problem developed using Aspen, a domain-specific language for performance modeling. The model focuses on the exploration of algorithmic tradeoffs, data structures and storage, and the impact of an important tiling factor in the image formation kernel of a synthetic aperture radar image-processing computation.